The Agency Cost of Internal Collusion and Schumpeterian Growth - Martimort, David; Verdier, Thierry (Review of Economic Studies, 2004)
This paper analyses the link between the internal organization of the firm and the growth process. We present a Schumpeterian growth model in which monopoly firms face agency costs due to collusion between managers inside the organization. These costs affect incentives to invest and the rate of innovation in the economy. When collusion is self-enforcing, higher growth and more creative destruction shortens in turn the time horizon of colluding agents in the organization and makes internal collusion more difficult to sustain. We analyse this two-way mechanism between growth and agency problems and show how the transaction costs of side-contracting within the firm and the growth rate of the economy are simultaneously derived.